Effects of cannabidiol on body weight and appetite: a systematic review - Joaquim Pedro Semide de Sousa Pinto (2022)
Background: Cannabidiol (CBD), one of the main components of the Cannabis sativa plant, is a non-psychotropic cannabinoid that has recently drawn the attention of researchers and clinicians for its potential therapeutic applications. In this systematic review we aim to describe the possible effects of CBD in both appetite and body weight. Methods: Both authors independently ran a thorough search in both MEDLINE and CENTRAL databases up to December 2021 and included every peer-reviewed, original randomized controlled clinical trial that reported data on either of said outcomes. Risk of assessment bias was performed with Cochrane's RoB2 tool and results were summarized in tables. Results: A total of 11 trials were included in this review. Of these, the majority reported on CBD reducing appetite and/or body weight or body mass index (BMI) whilst some have found no significant changes and one trial described an increase in appetite. Discussion: Most of the studies included in the present review raised some concerns in terms of risk of bias. We believe further research is needed in order to clarify potential mechanisms involved in the effect of CBD on feeding/appetite.